2014
DOI: 10.1002/anie.201311122
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Mesoporous Frameworks with Vanadoborate Clusters

Abstract: A new porous vanadoborate was synthesized by employing the scale chemistry theory with the vanadoborate cluster V10B28. The twofold interpenetrated lvt network was assembled with zinc-containing elliptical vanadoborate clusters and Zn polyhedra. The single lvt framework contains a three-dimensional 38×38×20 ring channel system with the pore size (24.7×12.7 Å) reaching the mesoscale, thus indicating the possibility of constructing 3D ordered mesopores with vanadoborate clusters. The porosity of the SUT-7 struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…52 Bond valence summation showed that vanadium has an average bond valence sum of approximately +4.2018 without any preferential occupancies for V 4+ and V 5+ in SUT-10, consistent with its dark green color. 40 This result was further confirmed by the XPS results with a peak at 516.3 eV with a shoulder beside, corresponding to V 4+ 2p 3/2 and V 5+ 2p 3/2 ( Figure S4). 41 Different from that of SUT-10, the bond valence summation for vanadium in SUT-11 clusters is +4.05, indicated by the slightly longer bond lengths and light green color ( Figure S6).…”
Section: Inorganic Chemistrysupporting
confidence: 68%
“…52 Bond valence summation showed that vanadium has an average bond valence sum of approximately +4.2018 without any preferential occupancies for V 4+ and V 5+ in SUT-10, consistent with its dark green color. 40 This result was further confirmed by the XPS results with a peak at 516.3 eV with a shoulder beside, corresponding to V 4+ 2p 3/2 and V 5+ 2p 3/2 ( Figure S4). 41 Different from that of SUT-10, the bond valence summation for vanadium in SUT-11 clusters is +4.05, indicated by the slightly longer bond lengths and light green color ( Figure S6).…”
Section: Inorganic Chemistrysupporting
confidence: 68%
“…2 The scope of such 25 frameworks is no longer limited to metal phosphates (such as aluminosilicate zeolites, aluminophosphates, zincophosphates and gallium phosphates), but instead to mainly include metal borates and their derivatives (such as metal borophosphates, 3 borogermanates 4 and borovanadates 5, 6 ). Resulting from the 75 structure with nonlinear optical properties. 9 (iii) V IVcontaining compounds have caused great interest owing to their inherent magnetism.…”
mentioning
confidence: 99%
“…The known vanadoborates have now been classified into the following four categories [24]:V 6 B 20 species containing a V 6 macrohexagon imbedded in a B 20 borate matrix, typically corresponding to a [V 6 B 20 O 50 H 8 ] 8− anion building block [2,3,25]. …”
Section: The High-spin Vanadoborate Analogue Of Benzenementioning
confidence: 99%